Synaptonemal Complex dimerization regulates chromosome alignment and crossover patterning in meiosis. - Spencer G Gordon; Lisa E Kursel; Kewei Xu; Ofer Rog (PLoS Genetics)
During sexual reproduction the parental homologous chromosomes find each other (pair) and align along their lengths by integrating local sequence homology with large-scale contiguity, thereby allowing for precise exchange of genetic information. The Synaptonemal Complex (SC) is a conserved zipper-like structure that assembles between the homologous chromosomes, bringing them together and regulating exchanges between them. However, the molecular mechanisms by which the SC carries out these functions remain poorly understood. Here we isolated and characterized two mutations in the dimerization interface in the middle of the SC zipper in C. elegans. The mutations perturb both chromosome alignment and the regulation of genetic exchanges. Underlying the chromosome-scale phenotypes are distinct alterations to the way SC subunits interact with one another. We propose a model whereby the SC brings homologous chromosomes together through two activities: obligate zipping that prevents assembly on unpaired chromosomes; and a tendency to extend pairing interactions along the entire length of the chromosomes.